Comparison of Gemcitabine Plus Cisplatin vs. Docetaxel Plus Fluorouracil Plus Cisplatin Palliative Chemotherapy for Metastatic Nasopharyngeal Carcinoma - Sun, Xue-Song; Wang, Xiao-Hao; Liu, Sai-Lan; Luo, Dong-Hua; Sun, Rui; Liu, Li-Ting; Guo, Shan-Shan; Chen, Qiu-Yan; Tang, Lin-Quan; Mai, Hai-Qiang (Frontiers in Oncology, 2020)
Objective: Our study aimed to compare the efficacy and toxicity of two chemotherapy regimens, gemcitabine plus cisplatin (GP) versus docetaxel plus, fluorouracil plus cisplatin (TPF), in metastatic nasopharyngeal carcinoma (NPC) patients. Materials and methods: We retrospectively enrolled metastatic NPC patients between July 2006 and December 2016 who were treated with TPF or GP palliative chemotherapy (PCT). The association between the PCT regimens and survival conditions was evaluated by log-rank tests and the Cox proportional hazard model. A cohort was created using propensity score matching with the ratio of 1:1 to clarify the results of the multivariable cox regression analyses. Overall survival (OS) was the primary endpoint. Results: Of 266 eligible patients, 186 and 80 patients respectively received TPF and GP regimen. No significant difference was demonstrated in the survival rate between the GP and TPF groups (3-year OS: 52.6% vs. 50.3%; P=0.929). However, multivariable analysis suggested receiving GP as an independent protective factor (HR, 0.864; 95% CI, 0.753–0.992; P=0.042). In the matched cohort, treatment with GP was also associated with a significantly higher OS (3-year OS: 52.6% vs. 35.6%, P=0.042). Subgroup analysis indicated that the superiority of GP reflected in patients with secondary metastases rather than primary metastases. The incidence of 3–4 treatment-related toxicity was more common in the TPF group than the GP group. Conclusion: Our study suggested that GP might be superior to TPF for metastatic NPC patients, especially those with secondary distant metastases. Further studies are necessary to validate our results.